If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 3x + -1 + -4 Reorder the terms: 16 = -1 + -4 + 3x Combine like terms: -1 + -4 = -5 16 = -5 + 3x Solving 16 = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 16 + -3x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 16 + -3x = -5 + 0 16 + -3x = -5 Add '-16' to each side of the equation. 16 + -16 + -3x = -5 + -16 Combine like terms: 16 + -16 = 0 0 + -3x = -5 + -16 -3x = -5 + -16 Combine like terms: -5 + -16 = -21 -3x = -21 Divide each side by '-3'. x = 7 Simplifying x = 7
| 352=8z | | (2x^2-3)=49 | | X^2+4x+4=49 | | 30+10x=80 | | 3x-2=9x+2 | | 7-13x=5x+13 | | 2(2x-1)=-1+(4x-1) | | 27-y^3=0 | | 9x+2=3x-2 | | 9x^2-6x-4=4 | | b+5-96=-48 | | 14x+8=17x-19 | | .40x=-4 | | 33j=198 | | 3x^2+5=32 | | 33j=197 | | b+8-96=-48 | | 216=n/2 | | 36=36p | | 4a-7=0 | | 45m=90 | | (-4)-s=0 | | (-9)=s+(-4) | | 60-g=6 | | (-10)=n-8 | | 36-x=7(7x+11)+9 | | (-2)-k=4 | | (-14)=r-6 | | 12n=-5 | | 9=j+7 | | -8+7x=7x-8 | | v+(-3)=(-10) |